Treatment-Free Remission in Real-World Chronic Myeloid Leukemia Patients: Insights from German Hematology Practices - Dengler, Jolanta; Tesch, Hans; Jentsch-Ullrich, Kathleen; Gerhardt, Anke; Schulte, Clemens; Lipke, Joerg; Loewe, Gunnar; Kiani, Alexander (Acta Haematologica, 2022)
Introduction: Treatment-free remission (TFR) is increasingly considered as treatment goal for patients with chronic myeloid leukemia (CML), but information on the disposition and outcome of TFR in clinical practice is scarce. Here, we report the characteristics of patients with CML in deep molecular remission (DMR) and/or after an attempt of TFR reported by 33 German hematologists. Methods: Data were collected retrospectively by means of a questionnaire. Patients were eligible if they had either discontinued tyrosine kinase inhibitor (TKI) therapy or had achieved DMR of at least MR4 (BCR-ABL =0.01%) prior to the time-point of data collection. Results: 797 patients were included in the analysis, out of which 281 patients had been discontinued from TKI treatment. TKI discontinuation rates among practices were variable, ranging from 0 to 36 patients. Mean time from TKI initiation to discontinuation was 7.2 years; mean duration of MR4 before TFR was 3.5 years. At the time of entering TFR, most patients (90.8%) had achieved a deep molecular response (>= MR4). BCR-ABL monitoring during TFR was performed heterogeneously: Within the first 6 months of TFR, 58.6% of the practices reported mean monitoring intervals of <6 weeks, while 20.7% employed intervals >8 weeks. After entering TFR, 53.2% of patients remained in MR4 or better. TKI treatment was reinitiated in 108 patients, mainly for loss of major molecular remission. Conclusions: These clinical data from a German real- life population show that TKI discontinuation is feasible in clinical practice. Outcomes appear to be comparable to those reported in clinical trials, but molecular monitoring in TFR is rather variable.
CRIS-Team WoS Importer:2023-01-27